2022
DOI: 10.1371/journal.pone.0267150
|View full text |Cite
|
Sign up to set email alerts
|

Using nanoemulsions of the essential oils of a selection of medicinal plants from Jazan, Saudi Arabia, as a green larvicidal against Culex pipiens

Abstract: Researchers are increasingly looking to plants as sources of novel ingredients active against vector-borne diseases. Medicinal plant extracts and their metabolites are an attractive source for such products. This study investigated the insecticidal activity of five essential oils extracted from the most common medicinal herbs in Jazan province, Kingdom of Saudi Arabia. Extracted oils and nanoemulsions synthesized from those oils were characterized before application at different concentrations to laboratory-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
6
0
3
Order By: Relevance
“…The spraying of insecticide indoors accounted for 60% of insecticide usage in vector control. The issues of resistance in adult vectors have diverted attention towards the use of growth regulators, bacterial and plant extracts in the control of immature stages of mosquitoes in their breeding habitats (Mahran 2022). Oil film made by the oil extracts of Azadirachta indica and many other plants was successful in killing immature stages of Anopheles, Culex, and Aedes mosquitoes (Ayinde et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The spraying of insecticide indoors accounted for 60% of insecticide usage in vector control. The issues of resistance in adult vectors have diverted attention towards the use of growth regulators, bacterial and plant extracts in the control of immature stages of mosquitoes in their breeding habitats (Mahran 2022). Oil film made by the oil extracts of Azadirachta indica and many other plants was successful in killing immature stages of Anopheles, Culex, and Aedes mosquitoes (Ayinde et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While there have been recent advances in the research of micro and nanoemulsions of caraway EO [93] and encapsulation of caraway EO [94][95][96][97], in most cases, the research lacks efficacy tests or comparisons with pure EO under the same testing conditions. Better nanoemulsion performance has been demonstrated in contact insecticide or larvicide testing, most likely due to the better penetration ability of the smaller EO particles in the emulsion [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The choice of surfactant affects the formation and performance of the emulsion. The contact toxicity of EO emulsions against various pests has shown higher mortality rates at lower applied doses [46][47][48][49] compared to non-formulated EOs. On the other hand, the fumigant toxicity of emulsions can be lower compared to nonformulated EOs [50,51].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical nature of the component elements in the essential oils influences the size of the particles obtained: when oxygenated monoterpenes and sesquiterpene hydrocarbons predominate in the oil component, smaller particles are obtained [36,40]; at the opposite pole are organosulfur compounds from garlic oil [40], phenylpropanoids and alkane hydrocarbon from clove oil [41].…”
Section: Nanostructured Formulations Of the Essential Oil-advantages ...mentioning
confidence: 99%
“…Nanoemulsification of the essential oils does not always increase the insecticidal effects on the target species. Mahran and collaborators [41] showed that this technique did not improve the performance of clove (Syzygium aromaticum (L.) Merr. & L. M. Perry (Myrtaceae)) and ginger (Zingiber officinalis Roscoe (Zingiberaceae)) oils on the larvae of Culex pipens L. (Diptera: Culicidae).…”
Section: Nanostructured Formulations Of the Essential Oil-advantages ...mentioning
confidence: 99%